EVALUASI SEISMIK BANGUNAN EKSISTING DENGAN METODE FEMA P-154 DAN FEMA 310 - Satria Putra Negara; Ridwan Ridwan; Zulfikar Djauhari (Jurnal Sains dan Teknologi, 2022)
This research studies how to apply the FEMA P-154 and FEMA 310 procedures to Indonesian Earthquake Map based on SNI 1726-2019 located in Bagansiapiapi City, Riau Province. The study conducted in accordance with the type of building based on FEMA, namely C1 (Concrete moment resisting frames), W2 (Wood frame commercial and industrial buildings). The object building consists of office buildings, religious facilities, health and historical relics in the City of Bagansiapiapi. Bagansiapiapi City is in a moderate-high earthquake zone (moderate high). At level 2 RVS, there are 6 buildings that have scores below the minimum limit or need further analysis, including Bappeda Office, DPRD Office, Health Office, Inspectorate Office, Al-Ihsan Mosque and Al-Ikhlas Mosque. Based on the results of Tier 1, the Regent's Office is the building object that has the most discrepancies. Based on the results of the spectrum response analysis that has been carried out on the research object the Regent's Office shows the structural behavior towards earthquake loads fulfilling the requirements stipulated in the earthquake building regulations SNI 1726-2019.